Visualization, Thematic Evolution, and Collaborative Networks of Vaping, E-Cigarettes, and Cancer: A Scientometric Analysis - Fran Espinoza-Carhuancho; Carlos Quispe-Vicuña; Julia Medina; Lucia Quispe-Tasayco; Diego Galarza-Valencia; Frank Mayta-Tovalino (Journal of Head & Neck Physicians and Surgeons)
Background: The aim of the study was to examine the visualization, thematic evolution, and collaborative networks of vaping, e-cigarettes, and cancer. Materials and Methods: A descriptive study with a scientometric approach was conducted by searching Scopus between January 2018 and May 2024. Metadata were exported to SciVal, a bibliometric analysis tool, to assess research productivity and impact. The bibliometric indicators used include the number of published papers per country/region (academic production), the average number of citations per publication (citations per publication), the average number of views per publication (views per publication), and the h-index. Results: The most productive journals were “Nicotine and Tobacco Research” and “Tobacco Control.” The most prominent institutions were New York University and the University of North Carolina at Chapel Hill. Most authors wrote only one paper, reflecting Lotka’s law. The United States led in terms of article production. Significant collaboration patterns were observed between different nations. Conclusion: The bibliometric study revealed trends in research on vaping, e-cigarettes, and cancer. The journals “Nicotine and Tobacco Research” and “Tobacco Control” led in productivity. “New York University” and the “University of North Carolina” at Chapel Hill were the top institutions. Globally, the United States led in article production. The findings can inform future research and policy.